A new genus and species of lappet moths (Lepidoptera: Lasiocampidae) from Central Asia with notes on the systematics of the family - Beljaev, Evgeniy A.; Gorbunov, Pavel Yu.; Korb, Stanislav K. (Zootaxa, 2025)
A new genus, Zolotuhia gen. nov., with the type species Zolotuhia paradoxa, sp. nov., from Kyrgyzstan, Talassky Mt. Range, is established in the lepidopteran family Lasiocampidae. The new genus is characterized by a surprising mix of features in the appearance, wing pattern, wing venation, male and female genitalia, shared with different groups of lappet moths. Based on the review of morphology in the Chondrosteginae/Poecilocampinae/Macromphaliinae lineage of Lasiocampidae, a tentative morphological phylogeny of the genera in the Chondrosteginae/Poecilocampidae group is proposed and two new synonyms: Chondrostegidae Tutt, 1902, = Poecilocampinae Tutt, 1902, syn. nov., = Trichiurinae Tutt, 1902, syn. nov., is established. The generic composition of Chondrosteginae s.l. is discussed. For Chondrostegoides nobilorum Zolotuhin, 2007 a new combination is established: Trichiurana nobilorum (Zolotuhin, 2007), comb. nov. For the dorsal dilation of the valve sacculus located lateral to juxta in Lasiocampidae, early inappropriately named as “valve saccular lobe”, a new name “dorso-basal saccular lobe” is offered. Some problems in the morphology, phylogeny and systematics of Lasiocampidae are addressed.